Characteristics of the vaginal microbiota with a combination of bacterial vaginosis with the pathology of the vagina and cervix inflammatory genesis - T Yu Pestrikova; E A Yurasova; A V Kotelnikova (IP Berlin A.V., 2017)
The article is devoted to investigation microbiocenosis of the genital tract reproductive age women with the combination of bacterial vaginosis together with pathology of vagina and cervix of the inflammatory genesis. The study of microbiota with bacterial vaginosis showed that the microflora is not identical, but at the same time, depends on the combination of bacterial vaginosis with other nosological forms (cervicitis, vulvovaginal candidiasis). The frequency of relapse with the combination of bacterial vaginosis with cervicitis and vulvovaginitis candidiasis was significantly higher than with a pure form of bacterial vaginosis. All this is important in choosing treatment methods. The combination of several nosological forms (bacterial vaginosis, cervicitis, vulvovaginal candidiasis) leads to a significant increase in adverse outcomes of pregnancy and childbirth.